Comparison of 2009 and 2011 WHO Guidelines, and Scoring Models for Adult Hospitalized Dengue Infection: A Single Observation in Tangerang, Indonesia - Wiwing, Veronica; Japutri, Josephine; Suryadinata, Neneng (Medicinus, 2024)
Background: World Health Organization (WHO) published a dengue guideline in 2009 and in 2011 by WHO-SEARO. However, many of dengue cases in early phase do not meet all the criteria by WHO classification. Because of this condition there is a scoring model that was published in 2015, that might help in primary health care. Therefore, a study to compare those diagnostic tools especially in adult dengue patients in Banten is needed.Aims: This study is to know the comparison between 2009 version and 2011 version of dengue diagnostic guidelines by WHO and scoring model version.Methods and Material: This study used a descriptive method with a cross-sectional design at 60 adult dengue patients. Each patient is grouped according to diagnostic tools’ classification and will be analyzed using Chi-square.Results: Results are grouped according to the WHO diagnosis from 2009 and 2011, presumptive model and probable models where there are 46 (77%), 48 (78%), 31(52%), and 15 (25%) of patients diagnosed with dengue infection. Overall, the diagnosis made by the 2009 WHO and the probable models has the most superior sensitivity and specificity values of 84,6% and 25%, and 82,4% and 97,7% respectively compared to other diagnostic tools. However, from the results of positive predictive values, probable models have a higher percentage than the 2009 WHO diagnosis.Conclusions: The probable model is more sensitive and specific than other diagnostic results. These conclude that probable model is best tool for dengue infection screening in early phase of infection.